2001
DOI: 10.2143/ac.56.6.2005702
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of myocarial involvement in systemic lupus erythematosus by signal-averaged electrocardiography and echocardiography

Abstract: The depolarization abnormalities, revealed by ECG-SA, probably reflect a longer extent of myocardial fibrosis in SLE patients with ECHO evidence of abnormal left ventricular filling. The simultaneous occurrence of ECHO and ECG-SA alterations could be a marker of subclinical myocardial involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Some stud-ies suggest that depolarization abnormalities on signalaveraged ECG accompanied by echocardiographic evidence of abnormal LV filling could reflect the presence of myocardial fibrosis and could be a marker of subclinical myocardial involvement in SLE patients. 301 Cardiac involvement can manifest itself by conduction system abnormalities such as complete atrioventricular heart block. Cardiac MR and myocardial strain and strain rate can identify patients with early manifestation of SLE-induced cardiomyopathy.…”
Section: 300mentioning
confidence: 99%
“…Some stud-ies suggest that depolarization abnormalities on signalaveraged ECG accompanied by echocardiographic evidence of abnormal LV filling could reflect the presence of myocardial fibrosis and could be a marker of subclinical myocardial involvement in SLE patients. 301 Cardiac involvement can manifest itself by conduction system abnormalities such as complete atrioventricular heart block. Cardiac MR and myocardial strain and strain rate can identify patients with early manifestation of SLE-induced cardiomyopathy.…”
Section: 300mentioning
confidence: 99%
“…Since the presence of anti-Ro/ SSA was related with a prolonged QTc, its presence in the global context of increased sympathetic activity and higher incidence of late potentials can be a determinant factor for sudden death due to arrhythmia. The presence of late potentials in high-resolution electrocardiogram (ECG-HR) was also documented in the study of Paradiso et al 30 in which 20% of the patients had this alteration compared with only 5.5% in the control group.…”
Section: 12mentioning
confidence: 69%
“…[14] Rosato et al found regional diastolic dysfunction by tissue doppler echocardiography in patients with systemic sclerosis (SSc) and Paradisp et al showed disturbed le ventricular lling patterns in SLE patients. [21,22] It is clear that le ventricular dysfunction is relatively frequent in in ammatory autoimmmune diseases. Myocardial dysfunction can be a result of myocarditis, myocardial brosis, vasculitis or microvascular dysfunction in these patients, but it can also be secondary to general subclinical or clinical in ammatory status.…”
Section: Discussionmentioning
confidence: 99%